(3eTcd EYQGH GdbQBf GdcQjes - (3nepqcj Hf CHj WGdH nMoqehT Hf eMeO Hf eNJGQ GdCfOdSj GdbjSj, CHh eMeO,J (B437 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efg ChGFd ShQI GdHbQI Hbhdg (B: (3bhdg (B" (3Pdc GdcJGH (B" (3GNJda Cgd GddZI hGdJaSjQ ai eYfi (B" (3Pdc (B" (3bGdJ WGFaI (B: (3Pdc ETGQI Edi GddhM GdeMahX s
(3BNQgG (B:s
(3bhdg (B" (3ef GdLfg hGdfGS (B" (3GdfGS MaWi YWa Ydi GdhShGS Ch ef TQ GdhShGS ced eTcd EYQGH GdbQBf deci Hf CHj WGdH s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B286 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B3s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdfMhs